Optimised information system reliability techniques for knowledge society acceptance. (26th January 2010) - Bardis, Nikolaos G.; Drigas, Athanasios; Doukas, Nikolaos; Karadimas, Nikolaos V.
Two important obstacles averting the widespread adoption of knowledge society and e-government technologies in communities are distrust in their reliability and fear of the costs to be incurred. In order to overcome these obstacles, algorithmic advances are required that improve reliability of information systems without increasing their cost. In this paper a new approach to increase the reliability and effectiveness of transient error detection using checksum calculations is proposed, that is based on the optimisation of coding with special differential Boolean transformations. Two methods for obtaining such transformations are developed and examples of coding for checksum functions are given. The new methods are equivalent in terms of computational cost as classical checksum approaches.